Pendidikan Sufistik Syeikh Nuruddin Ar-Raniry - Mulia Sari; Yusran Sardi; Muhammad Ridho Agung (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The concept of Sufistic education carried out by Nuruddin Ar-Raniry in Aceh is to make shari'at one of the characteristics of his Sufistic teachings (akhlaqi). Shari'at is a valid rule in worshiping Allah. The formulation of the problem in this study departs from the researcher's curiosity to know about the biography and concept of Sufistic education of Nuruddin Ar-Raniry. This research is a qualitative research that is oriented towards library research. The data collection technique used by researchers in this research is through documentation activities, namely seeking various information about Nuruddin Ar-Raniry contained in books, theses, journals and other readings. This study aims to find out the biography and monumental works written by Nuruddin Ar-Raniry. This research also aims to explore the teachings of Sufistic education Nuruddin Ar-Raniry and his contribution to the development of Islamic teachings, especially in Sufistic education. The results of this study indicate that Nuruddin Ar-Raniry's concept of sufistic education, among other things, emphasizes aspects of the implementation of the Shari'a (worship) as the teachings of Sufism with an akhlaqi pattern, not equating creatures with God both in terms of Shari'a and hakikat, understanding the role of humans as khalifah fil 'ardh and acknowledging the existence of human beings. Keywords: Concept, Sufistic Education, Nuruddin Ar-Raniry